2013
DOI: 10.1111/jfb.12171
|View full text |Cite
|
Sign up to set email alerts
|

Excess post‐hypoxic oxygen consumption in Atlantic cod Gadus morhua

Abstract: Atlantic cod Gadus morhua experienced oxygen deficit ( D O 2 ) when exposed to oxygen levels below their critical level (c. 73% of pcrit) and subsequent excess post‐hypoxic oxygen consumption (CEPHO) upon return to normoxic conditions, indicative of an oxygen debt. The mean ± s.e. CEPHO: D O 2 was 6·9 ± 1·5, suggesting that resorting to anaerobic energy production in severe hypoxia is energetically expensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…In [67], using tagged Baltic cod individuals, it was shown that cod visit hypoxic waters, briefly but frequently, probably in search of benthic preys [65], which generally are more tolerant to hypoxia than fish [68], providing support for the occurrence of this mechanism. According to this interpretation, as most fish avoid oxygen concentrations that would decrease their growth [25], in our analyses 1 ml l −1 could be considered as a sub-lethal threshold that cod tend to avoid when not feeding in deeper layers with an oxygen concentration even lower.…”
Section: Discussionmentioning
confidence: 99%
“…In [67], using tagged Baltic cod individuals, it was shown that cod visit hypoxic waters, briefly but frequently, probably in search of benthic preys [65], which generally are more tolerant to hypoxia than fish [68], providing support for the occurrence of this mechanism. According to this interpretation, as most fish avoid oxygen concentrations that would decrease their growth [25], in our analyses 1 ml l −1 could be considered as a sub-lethal threshold that cod tend to avoid when not feeding in deeper layers with an oxygen concentration even lower.…”
Section: Discussionmentioning
confidence: 99%
“…While this is a problem common to all experimental systems, there does not appear to be a universally accepted technique for how to measure and mathematically correct for it. It is often stated in papers, for instance, that Ṁ O 2 been corrected for background respiration, yet details of the procedure are often scant (Plambech et al , ) or entirely missing (Scarabello et al , ; Schurmann & Steffensen, ; Steffensen et al , ; Casselman et al , ). Even in cases where techniques are mentioned, they appear to vary widely.…”
Section: Calculating Oxygen Consumption (ṁO2) Using Intermittent‐flowmentioning
confidence: 99%
“…For instance, if the experimenter wants to test the effect of hypoxia by letting the partial pressure of oxygen ( p O 2 ) decrease by 15–16 kPa in the chamber, carbon dioxide, which has a 25–30 times higher solubility than oxygen, will increase by 0·5–0·6 kPa, a level that is more than even the worst case global change scenario (Stocker et al , ). Further, if the closed‐system measurement period has resulted in prolonged hypoxia and the fish has had to rely on anaerobic metabolism, this will raise aerobic metabolism during the next flush and measurement cycle as a result of excess post‐hypoxia oxygen consumption (EPOC) arising from the anaerobic metabolism (Scarabello et al , ; Svendsen et al , ; Plambech et al , ). Finally, any of the factors listed can stimulate spontaneous activity, or physiological responses, resulting in oxygen consumption ( Ṁ O 2 ) measurements that do not reflect the animal's oxygen consumption at SMR (Keys, ; Forstner, ; Gnaiger, ; Steffensen, ).…”
Section: Introductionmentioning
confidence: 99%
“…The species is known to completely avoid hypoxic waters in the Kattegat, Baltic Sea and Gulf of St Lawrence when their metabolic scope approaches zero (Chabot & Claireaux, 2008). Satellite archival tagging and laboratory experiments have shown that Atlantic blue marlin Makaira nigricans Lacépède 1802 can also tolerate low oxygen if necessary and dive into low oxygen waters for short durations to catch prey (Neurenfeldt et al, 2009;Stramma et al, 2011;Plambech et al, 2013).…”
Section: Behavioural Responsesmentioning
confidence: 99%